Pengaruh Tingkat Pengetahuan dan Stres Kerja terhadap Pencegahan Kecelakaan Kerja pada Pekerja Giling dan Ketel di PG Rejo Agung Baru Madiun - Caesar Kridha Bagus Prahartiko; FX Ady Soesetijo; Ristya Widi Endah Yani (Multidisciplinary Journal, 2019)
workers in sugar mills are prone to accident in their workplace. This research aims at disclosing the effect of knowledge level and work stress on prevention of work accident in Milled and Kettle Workers. It is a qualitative research employing analytic observation method using cross sectional design. The sample, including 115 workers in Milling and Kettle Section in PG Rejo Agung Baru Madiun, were selected by using total sampling. Regression Test by SPSS 22 was applied to analyze the data. Findings demonstrate the sig value of knowledge level indicating 0.889 and sig value of stress level of 0.027. It reveals that there is no effect from workers’ knowledge level, in contrast, work stress affect the prevention of work place accident. Therefore, more stimulation on knowledge level and support for workers are prominent to minimize their work stress.Keywords: Knowledge level, sugar mill, work accident, work stress